Question

\( x^{2}-3 x y+2 y^{2}=4 \) and \( 3 x-2 y=0 \)

Ask by Christensen Daniel. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \((-2,-3)\) and \((2,3)\).

Solution

Solve the system of equations \( x^{2}-3x*y+2*y^{2}=4;3x-2y=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x^{2}-3xy+2y^{2}=4\\3x-2y=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x^{2}-3xy+2y^{2}=4\\x=\frac{2y}{3}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(\frac{2y}{3}\right)^{2}-3\times \frac{2y}{3}y+2y^{2}=4\) - step3: Simplify: \(\frac{4}{9}y^{2}=4\) - step4: Multiply by the reciprocal: \(\frac{4}{9}y^{2}\times \frac{9}{4}=4\times \frac{9}{4}\) - step5: Multiply: \(y^{2}=9\) - step6: Simplify the expression: \(y=\pm \sqrt{9}\) - step7: Simplify: \(y=\pm 3\) - step8: Separate into possible cases: \(y=3\cup y=-3\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2y}{3}\\y=3\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2y}{3}\\y=-3\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=2\\y=3\end{array}\right.\cup \left\{ \begin{array}{l}x=-2\\y=-3\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=3\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=-3\end{array}\right.\cup \left\{ \begin{array}{l}x=2\\y=3\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-2,-3\right)\cup \left(x,y\right) = \left(2,3\right)\) The solutions to the system of equations \(x^{2}-3xy+2y^{2}=4\) and \(3x-2y=0\) are \((-2,-3)\) and \((2,3)\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve these two equations, let’s start with the second equation, \( 3x - 2y = 0 \). This simplifies to \( y = \frac{3}{2}x \). Now, we can substitute this expression for \( y \) into the first equation. Now substitute \( y \) into \( x^{2} - 3xy + 2y^{2} = 4 \): \[ x^{2} - 3x\left(\frac{3}{2}x\right) + 2\left(\frac{3}{2}x\right)^{2} = 4 \] \[ x^{2} - \frac{9}{2}x^{2} + 2\left(\frac{9}{4}x^{2}\right) = 4 \] \[ x^{2} - \frac{9}{2}x^{2} + \frac{9}{2}x^{2} = 4 \] Combining the \( x^{2} \) terms yields \( 0 = 4 \), which is a contradiction. Thus, the two equations do not intersect in real numbers, meaning there are no solutions for \( (x, y) \) that satisfy both equations simultaneously. So in a nutshell, you've got a pair of equations that just don't play well together!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy